Protecting Public Health and Biodiversity from Electromagnetic Exposure Through Spatiotemporal Management of Emissions in Connected Social Spaces - Adel Razek (Bioelectromagnetics in Medicine, 2026)
Modern technologies using electromagnetic fields (EMF) present both anticipated benefits and undesirable side effects related to exposure. These effects may pose potential health risks to humans and environmental biodiversity under specific exposure conditions. Diverse public spaces where people work, play, do business, attend school, or receive healthcare each possess their own unique biodiversity. The functioning of these spaces requires internet connections via antennas, which are themselves linked to management and security systems, as well as telecommunications equipment. These connectivity needs are closely tied to, among other things, the presence of people and depend on operating conditions such as the time of day and season. The base station antenna providing internet coverage is a source of EMF radiation. This coverage-exposure relationship can be controlled, enabling reliable temporal and spatial emissions, thus ensuring the necessary connections and protecting potentially exposed objects at a specific location and time. This allows for effective protection of public health and biodiversity against these exposures affecting public spaces and lifestyles. This paper proposes a perspective (conceptual proposal) for smart digital-assisted spatiotemporal management of electromagnetic emissions in connected public spaces. It aims to study and highlight the effects of exposure to EMFs on public health and biodiversity, as well as the importance of regular monitoring of emissions according to operational conditions, through the implementation of an autonomous emission procedure, assisted by artificial intelligence (AI) and supervised by digital twins (DTs). The sections of this article address base station antenna infrastructures, coverage and exposure strategy, the biological effects of exposure to EMFs on living tissues, the autonomous emission-exposure procedure, the AI-assisted augmented procedure, DT monitoring of the procedure, as well as the discussion and conclusions. The various themes addressed in this contribution are supported by literature reviews that facilitate understanding.